2017
DOI: 10.1016/j.colsurfa.2017.07.085
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence stability of water-in-oil drops: Effects of drop size and surfactant concentration

Abstract: We study the effects of (1) drop size; (2) surfactant chain-length and concentration; and (3) viscosity of the oil phase on the stability of water drops, pressed by gravity towards planar oilwater interface. The experimental results show that at low surfactant concentrations (around and below the CMC) the drop lifetime is controlled by the drainage time of the oily film, viz. by the time for reaching the critical film thickness at which this film ruptures. The small drops coalesce before the formation of a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 27 publications
9
56
0
Order By: Relevance
“…Finally, bubbles having an equivalent radius corresponding to Bo 5 have a smaller lifetime, which can be rationalized by a too small "rigidity" parameter, Λ = Ma/Bo 0.05. It should be noted that, experimental and theoretical studies on the lifetime of drops beneath a free surface have shown that, for large drops, Bo 1, the lifetime increases with their size [37,38,39] while, as seen in this study and the one of Nguyen et al (2013), the lifetime of bubbles decreases with their size for Bo 1 (see Fig 6a of Nguyen et al (2013)). In the case of drops, the inner liquid viscosity might not be negligible when compared to the outer phase viscosity.…”
Section: Drainage With Surfactantssupporting
confidence: 68%
See 1 more Smart Citation
“…Finally, bubbles having an equivalent radius corresponding to Bo 5 have a smaller lifetime, which can be rationalized by a too small "rigidity" parameter, Λ = Ma/Bo 0.05. It should be noted that, experimental and theoretical studies on the lifetime of drops beneath a free surface have shown that, for large drops, Bo 1, the lifetime increases with their size [37,38,39] while, as seen in this study and the one of Nguyen et al (2013), the lifetime of bubbles decreases with their size for Bo 1 (see Fig 6a of Nguyen et al (2013)). In the case of drops, the inner liquid viscosity might not be negligible when compared to the outer phase viscosity.…”
Section: Drainage With Surfactantssupporting
confidence: 68%
“…In that respect, the drainage of a liquid film on the top of a bubble is expected to have a different dynamics when compared to drops. For example, while Nguyen et al (2013) found that the lifetime of a large bubble decreases as the size of the bubble increases, studies on drops showed the opposite [37], [38], [39].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the coalescence of droplets could be accelerated by changing operating parameters such as temperature and electric field. The investigation of the size distribution of liquid droplets and droplet coalescence stability is of high importance in water-oil two-phase dispersed flow [ 20 ]. Fortelný et al reviewed the applicability of droplet diameter distribution in the processing of immiscible polymer blends [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The validity of the model was demonstrated by applying it to a range of model problems. In the same year, Politova et al (2017) studied the effects of drop size and viscosity of the oil phase on the stability of water drops moving towards a planar oil-water interface. They found small drops coalescence to occur before formation of a planar film at the interface.…”
Section: Introductionmentioning
confidence: 99%